Active and Passive Smart Structures and Integrated Systems XVII 2023
DOI: 10.1117/12.2658694
|View full text |Cite
|
Sign up to set email alerts
|

Making a brain on a structure: a conceptual study of elastic wave field neural networks for structural health monitoring

Abstract: The purpose of this study is to develop a novel concept of smart structural systems that can recognize their own structural integrity by an embodied high density sensor network. Over the past two decades, sensor networks for automatic inspection application have been intensively investigated, and it has now become reasonable to deploy over 1000 sensor nodes in a single structural system. It would be certain, however, that the current approaches that require rich electronics and wireless communication at each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Among the parities from the 1st to the 5th, it is found that the 2nd parity is the most sensitive to damage. This is the same as the result reported in the previous study (Masuda et al, 2023). The reason why the 1st parity is less sensitive than the 2nd parity may be due to the simplicity of the task, which could introduce the trained PRC some undesirable tolerance to the parameter variation.…”
Section: Damage Detection and Localizationsupporting
confidence: 88%
See 4 more Smart Citations
“…Among the parities from the 1st to the 5th, it is found that the 2nd parity is the most sensitive to damage. This is the same as the result reported in the previous study (Masuda et al, 2023). The reason why the 1st parity is less sensitive than the 2nd parity may be due to the simplicity of the task, which could introduce the trained PRC some undesirable tolerance to the parameter variation.…”
Section: Damage Detection and Localizationsupporting
confidence: 88%
“…Figure 1 illustrates the concept and entire workflow of the PRbased SHM proposed by the authors (Masuda et al, 2023).…”
Section: Concept Of Pr-based Shmmentioning
confidence: 99%
See 3 more Smart Citations